Research on the Mechanical Properties of New Double-Row Pile Supporting Structure Based on an In Situ Study. (1st June 2021) - Zhou, Yijun; Liu, Kuiming; Wang, Fengnian
Abstract : According to the force characteristics of the double-row pile supporting structure, two new types of double-row piles are developed: the prestressed strong-constrained double-row piles and the recycling assembled double-row piles. A comparative field test was conducted on the support effects of the two new double-row piles and conventional double-row piles. The test site is located in a deep foundation pit of the Beijing Daxing International Airport Project. The feasibility and reliability of the two new support structures are verified. Field monitoring included section strain and bending moment of the pile body, horizontal displacement of the pile body, and vertical and horizontal displacement of the pile top. The research shows that because of the prestressed anchorage cables in the rear row piles, the prestressed strong-constrained support structure can provide better tensile performance from the rear piles, and the deformation and displacement are minimal. The recycling assembled double-row piles have similar deformation and displacement to the conventional piles. Through the connection of the steel members, the construction time can be effectively shortened. After the backfill of the foundation pit, the steel members can be recycled and the cost can be reduced.